2017
DOI: 10.1101/cshperspect.a026187
|View full text |Cite
|
Sign up to set email alerts
|

InheritedTP53Mutations and the Li–Fraumeni Syndrome

Abstract: Li-Fraumeni syndrome (LFS) is a complex hereditary cancer predisposition disorder associated with early-onset cancers in diverse tissues of origin. Germline mutations are identified in 75% of patients with classic LFS. The lifetime likelihood of a mutation carrier developing cancer approaches 75% in males and almost 100% in females. Several genetic modifiers have been implicated to account for the phenotypic variability within and across LFS families; however, efforts to develop predictive algorithms of age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
147
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(153 citation statements)
references
References 51 publications
3
147
0
3
Order By: Relevance
“…The cancer predisposition syndrome that would come to be known as Li -Fraumeni syndrome (LFS; OMIM #151623, omim.org) was initially identified among families with a high incidence of childhood cancers, particularly sarcomas, early-onset cancers, and multiple primary tumors (Li and Fraumeni 1969; see also the review by Guha and Malkin 2016). An epidemiological link between germline TP53 mutations and LFS was made shortly after the discovery of p53, as it was realized that sporadic forms of the same types of cancers observed in patients with clinical features of LFS carried somatic inactivation of TP53 (Malkin et al 1990;Srivastava et al 1990).…”
Section: Germline Tp53 Mutations and Cancer Predispositionmentioning
confidence: 99%
“…The cancer predisposition syndrome that would come to be known as Li -Fraumeni syndrome (LFS; OMIM #151623, omim.org) was initially identified among families with a high incidence of childhood cancers, particularly sarcomas, early-onset cancers, and multiple primary tumors (Li and Fraumeni 1969; see also the review by Guha and Malkin 2016). An epidemiological link between germline TP53 mutations and LFS was made shortly after the discovery of p53, as it was realized that sporadic forms of the same types of cancers observed in patients with clinical features of LFS carried somatic inactivation of TP53 (Malkin et al 1990;Srivastava et al 1990).…”
Section: Germline Tp53 Mutations and Cancer Predispositionmentioning
confidence: 99%
“…In 1990, germline mutations in the TP53 gene were identified in affected members of selected kindreds; since then TP53 germline mutations have been identified in multiple LFS families . Approximately 75% of families meeting criteria for classic LFS have a genetic germline defect in TP53 . Cancer risk for LFS family members increases with age: a recent publication demonstrated a 50% risk by the age of 31 years for females, 46 years for males, and a 100% risk by the age of 70 for both genders .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Approximately 75% of families meeting criteria for classic LFS have a genetic germline defect in TP53. 5 Cancer risk for LFS family members increases with age: a recent publication demonstrated a 50% risk by the age of 31 years for females, 46 years for males, and a 100% risk by the age of 70 for both genders. 6 Bougeard et al recently published on a cohort of 1,730 French patients with LFS and showed that the cumulative incidence of childhood-onset cancer was 22% by age 5 years and 41% by age 18.…”
mentioning
confidence: 99%
“…The hereditary cancer predisposition of childhood cancer survivors may be missed for many reasons: (1) new hereditary syndromes being identified since their diagnosis, (2) appropriate tests being unavailable at the time they were originally seen, or (3) because new family cancers have arisen as the child has matured, changing the pedigree and possibly increasing estimated cancer risk . Yet, survivors may benefit from family history assessment and genetic testing even years after their cancer diagnosis, especially if the results guide long‐term care and surveillance (as an example, childhood cancer survivors identified as having Li–Fraumeni syndrome have a high risk of multiple future malignancies) …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Yet, survivors may benefit from family history assessment and genetic testing even years after their cancer diagnosis, especially if the results guide long-term care and surveillance (as an example, childhood cancer survivors identified as having Li-Fraumeni syndrome have a high risk of multiple future malignancies). 10 Knapke et al 12 reported that up to 29% of 370 screened childhood cancer survivors were suitable for genetics referral, 61% of whom were identified because of their family history of cancer. Knapke et al's study 12 and other studies 1,8 therefore advocate for regular (annual) family history review as a standard element in survivors' ongoing care.…”
Section: Introductionmentioning
confidence: 99%